The utility of head CT scans in geriatric patients with hip fractures following a low energy injury mechanism: A retrospective review. Issue 6 (June 2021) - Allen, James; Ravichandiran, Kajeandra; McLaughlin, Terry-Lyne; MacDonald, Christie; Howard, James; Lanting, Brent; Vasarhelyi, Edward
Highlights: 2114 patients were reviewed. 26.9% ( n  = 502) of the patients had a CT head scan as part of their workup. Sixty-two patients (12.3% of patients who received a CT scan or 2.9% of the study population) were found to have had an acute intracranial bleed. Zero patients required neurosurgical intervention following diagnosis of an acute bleed. Nine (14.5% of patients with a positive CT head) had thromboprophylaxis modification. Abstract: Objectives: Hip fractures are common low-energy orthopaedic injuries in the geriatric population. The purpose of this study is to determine the frequency of CT head exams and the incidence of clinically significant intracranial bleed in patients with low energy hip fractures. Design: A retrospective cross-sectional review was completed to identify hip fractures presenting to an academic health centre between 2006 and 2015. Our inclusion criteria were those patients with low energy hip fractures and medical records were reviewed to determine whether a CT head scan was utilized as part of their workup. Results: A total of 2114 patients were reviewed with an average age of 83.2 years. Hip fractures were treated with a hemiarthroplasty in 59.1% of the patients and with a dynamic hip screw in 40.9% of the patients. 26.9% ( n  = 502) of the patients received a CT head scan as part of their workup. Sixty-two patients (12.3% of patients who received a CT scan or 2.9% of the study population) were found to have had an acute intracranial bleed. None of these patients required neurosurgical intervention and only 9 (14.5% of patients with a positive CT head) had a modification to their thromboprophylaxis post-op. Of the 15 (26.4%) patient on home anticoagulation for a pre-existing medical condition, 10 (67%) had a delay in reinitiating their anticoagulation greater than 24 h post-operatively. Conclusion: During the study period, 26.7% of patients received a CT scan, with only 2.9% of patients suffering from a concurrent intracranial bleed. None of the patients with a positive scan required neurosurgical intervention, and scan results did not routinely alter DVT prophylaxis. Resuming home anticoagulation was delayed greater than 24 h post-operatively in ten (67%) of cases. With the challenges of resource allocation, potential delays to surgery and costs associated with CT scans, these investigations should be reserved for patients who have a history or physical exam findings of head trauma or are on anticoagulation pre-injury in the low energy hip fracture population. Level of Evidence: Level III